2004
DOI: 10.1097/01.tp.0000132324.14207.8b
|View full text |Cite
|
Sign up to set email alerts
|

Description of B Lymphocytes and Plasma Cells, Complement, and Chemokines/Receptors in Acute Liver Allograft Rejection

Abstract: The significant increase of B lymphocytes and plasma cells during acute rejection, together with the lack of a significant increase of proliferating cells, indicates that the migration of B lymphocytes and plasma cells-promoted by the expression of B-cell activating chemokines/receptors-plays a key role in acute liver rejection. The C4d deposits along the portal capillaries indicate a humorally mediated alloresponse caused by the accumulated B and plasma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 25 publications
5
54
1
1
Order By: Relevance
“…Yang et al showed that HBD-1 is chemotactic for dendritic cells and T-cells via the CCR6 chemokine receptor (24). Intriguingly, CCR6 expressing cells have been demonstrated in liver transplant recipients with acute rejection (25).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al showed that HBD-1 is chemotactic for dendritic cells and T-cells via the CCR6 chemokine receptor (24). Intriguingly, CCR6 expressing cells have been demonstrated in liver transplant recipients with acute rejection (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, no comprehensive analysis of capillary C4d staining in liver allograft biopsies has been performed. In a recent preliminary study, Krukemeyer et al found C4d deposits along the portal capillaries of biopsy specimens from patients with acute liver allograft rejection (59). However, no correlation with anti-donor antibodies was performed.…”
Section: Humoral Rejection In Other Solid Organ Allograftsmentioning
confidence: 96%
“…The presence of CD20 + B cells correlated with glucocorticoid resistance and graft loss. B cell infiltrates have also been described in human liver transplants undergoing AR (21), as well as cardiac transplants (22,23).…”
Section: B Cells In Allograft Rejectionmentioning
confidence: 98%